Pesticidal activity of Smilax zeylanica L. extracts on Cryptolestes pusillus (Schon.) (Coleoptera: Cucujidae) (Journal of Bangladesh Academy of Sciences, 2011)
The chloroform and methanolic extracts of Smilax zeylanica L. were assessed for mortality against the adults of flat grain beetle, Cryptolestes pusillus (Schon.) under laboratory conditions by the surface film method. The methanolic extracts caused significantly high (p < 0.001) mortalities than the chloroform extracts. The calculated LD50 values of the chloroform extracts of S. zeylanica on C. pusillus were 71.20, 67.06 and 62.22 μg/cm2 for leaf; 14.49, 11.41 and 7.9 μg/cm2 for stem; and 6.43, 4.67, 2.40 μg/cm2 for root extracts. But the LD50 values of the methanolic extracts were 39.79, 19.39 and 22.06 μg/cm2 for leaf; 14.27, 12.68 and 10.85 μg/cm2 for stem; and 12.58, 5.83 and 4.32 μg/cm2 for root extracts after 24, 48 and 72 hr post-exposure, respectively. Results obtained show the potential of using S. zeylanica extracts for C. pusillus management. Key words: Smilax zeylanica; Pesticidal activity; Cryptolestes pusillus DOI: 10.3329/jbas.v34i2.6867Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 201-203, 2010